Desenvolvimento de instrumentação eletrônica portátil para medida de pH em campo por meio de sensor óptico à base de filme de Polianilina - Vendramini, Gabriel (Universidade Federal de São Carlos, 2014)
The pH measurement has an important role in biotechnological processes as enzymatic reactions, fermentation processes and others. This ways the general objective of this work is therefore the development of a portable electronic instrumentation for reading in field an optical pH sensor based on a conductive polymer. The polyaniline, when used as an active element of the sensor it has useful electro-optical intrinsic properties for the measurement of pH in the range of 2 to 12 properties. Thus, the chemical synthesis of the sensor has been reproduced and the spectroscopy in the UV - Vis has been used for its characterization. For the electronic instrumentation, the colorimetric transducer comprises an "Emitted Ligth Diode" (LED) type "Red, Green, Blue" (RGB), and a light sensor was proposed to measure the attenuation caused by the sensor optical positioned between the sender and receiver of the light beam. The calibration method of the optical assembly was efficient, as the response curve obtained. For the evaluation of the instrument with the sensor, repeatability and reproducibility of assays were performed by calculating the respective standard deviations. The results in terms of precision and accuracy were satisfactory for measuring in the range of 2-12. Thus, a microcontrolled, functional and low cost electronic instrument was developed, presenting relevant advantages such as no need for a reference sensor and no susceptibility to electromagnetic interference. Against commercial equipments, the instrument has significant potential and it presents some possibilities of pH measurements in field applied to biotechnology, agricultural and others.
Keywords: Instrumentação eletrônica; Sensor de pH; Sensor óptico; Polianilina; Electronic instrumentation; pH sensor; Optical sensor; Polyaniline; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA DE PROCESSOS E SISTEMAS